Widening Socioeconomic and Racial Disparities in Cardiovascular Disease Mortality in the United States, 1969-2013 - Gopal K. Singh, PhD; Mohammad Siahpush, PhD; Romuladus E. Azuine, DrPH, RN; Shanita D. Williams, PhD, RN, MPH (Global Health and Education Projects, Inc., 2015)
Objectives: This study examined trends and socioeconomic and racial/ethnic disparities in cardiovascular disease (CVD) mortality in the United States between 1969 and 2013. Methods: National vital statistics data and the National Longitudinal Mortality Study were used to estimate racial/ethnic and area- and individual-level socioeconomic disparities in CVD mortality over time. Rate ratios and log-linear regression were used to model mortality trends and differentials. Results: Between 1969 and 2013, CVD mortality rates decreased by 2.66% per year for whites and 2.12% for blacks. Racial disparities and socioeconomic gradients in CVD mortality increased substantially during the study period. In 2013, blacks had 30% higher CVD mortality than whites and 113% higher mortality than Asians/Pacific Islanders. Compared to those in the most affluent group, individuals in the most deprived area group had 11% higher CVD mortality in 1969 but 40% higher mortality in 2007-2011. Education, income, and occupation were inversely associated with CVD mortality in both men and women. Men and women with low education and incomes had 46-76% higher CVD mortality risks than their counterparts with high education and income levels. Men in clerical, service, farming, craft, repair, construction, and transport occupations, and manual laborers had 30-58% higher CVD mortality risks than those employed in executive and managerial occupations. Conclusions and Global Health Implications: Socioeconomic and racial disparities in CVD mortality are marked and have increased over time because of faster declines in mortality among the affluent and majority populations. Disparities in CVD mortality may reflect inequalities in the social environment, behavioral risk factors such as smoking, obesity, physical inactivity, disease prevalence, and healthcare access and treatment. With rising prevalence of many chronic disease risk factors, the global burden of cardiovascular diseases is expected to increase further, particularly in low- and middle-income countries where over 80% of all CVD deaths occur.